Comparison of the efficacy of a neutral wrist splint and a wrist splint incorporating a lumbrical unit for the treatment of patients with carpal tunnel syndrome. (October 2016) - Golriz, Batol; Ahmadi Bani, Monireh; Arazpour, Mokhtar; Bahramizadeh, Mahmood; Curran, Sarah; Madani, Seyed Pezhman; Hutchins, Stephen W
Background: Different types of splints have been used as a conservative intervention to improve symptoms in patients with Carpal tunnel syndrome (CTS). Although a number of studies have been undertaken to compare different splints, information and understanding of the influence of these interventions are lacking. Objectives: The purpose of this study was to compare the effect of a classic thermoplastic wrist splint or a wrist splint with an additional metacarpophalangeal unit on pain, function, grip strength, and pinch strength in patients with mild-to-moderate carpal tunnel syndrome. Study design: Quasi experimental design. Methods: A total of 24 patients received conservative treatment using either the classic wrist splint or the wrist splint with the metacarpophalangeal unit for a period of 6 weeks. Primary outcome measures were pain, function, grip strength, and pinch strength. Data were collected immediately before and after using the two types of splints at baseline (0 weeks) and 6 weeks. Statistical analysis was performed using the paired t-test and an independent t-test. Results: Compared to baseline, both the classic thermoplastic wrist splint and the wrist splint with a metacarpophalangeal unit significantly decreased pain and increased function, pinch strength, and grip strength. Comparisons of the two types of splints for grip strength ( P  = 0.675) and pinch strength ( P  = 0.650) revealed that there were no significant differences between the two after 6 weeks of wear. However, there were significant differences in pain levels ( P  = 0.022) and the Disability of the Arm, Shoulder, and Hand score ( P  = 0.027) between the two types of splints from baseline to 6 weeks. Conclusion: The wrist splint with a metacarpophalangeal unit was more effective than the classic thermoplastic wrist splint in pain reduction and improvement of function. Clinical relevance: A wrist splint with a metacarpophalangeal unit may be an appropriate conservative treatment in the rehabilitation of patients with mild-to-moderate carpal tunnel syndrome.